Parameters Affecting Bulk Etch Rate VBfor CR-39 Detector - Khalid R. Flaih (مجلة جامعة الانبار للعلوم الصرفة, 2020)
In this work, the dependence of the bulk etches rate VB for CR-39detector on thetemperature T, etching time t and concentration N of the NaOH etchant solution has been studied fordetectors material types PADC. The concentration, etching time, temperatureand other conditions havebeen varied in the ranges (5.25-8.25) N, (1-5) hand (60-80) °C for PADC respectively. In this case, the thickness of material removed by etching ranges from 0.20 to 6.10